Optimization of Sharia Auidit of Islamic Financial Institutions on Employee Performance at Bank Syariah Mandiri Bondowoso - kurniawan ramdhani (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This study aims to determine the extent of the implementation of sharia audits on Islamic financial institutions in reviewing employee performance. In addition, the function of sharia audits is to control the supervision system, examining sharia financial institutions so that they remain in compliance with sharia principles in the application of audits. This research method uses descriptive qualitative methods in the assessment of the state of the research object. In the end, a conclusion will be drawn and described with a theory that is already in force and with regard to the object of research. The results of this study are the application of the concept of good corporate governance in the sharia aideit process at BSM Bondowoso where the intended concept is the application of sharia principles as compliance in the employee performance audit process applied by BSM Bondowoso, while the sharia audit process itself is reviewed from several values ​​among fairness, partnership, openness, the application of values ​​is carried out by the internal supervisor when conducting the audit process by the internal supervisor to all employees without fail. In the concept of good corporate governance, it is not only focused on the implementation of the sharia audit process, even BSM Bondowoso gives rewards and punishments to employees who apply sharia principles and compliance and maintain the good name and advance BSM Bondowoso and serve customers optimally and serve professionally by implementing values ​​of siddiq, fathanah, professional as the slogan and work culture of BSM Bondowoso. It can be concluded that the implementation of sharia audits on BSM employee performance is applied to all employees without exception of sharia principles, while the concept of good corporate governance is evaluated in terms of employee performance applying the principles of justice, partnership, and openness carried out by internal supervisors. In addition, BSM Bondowoso provides rewards and punishments to employees who have helped develop BSM Bondowoso progress and work professionally and apply Siddiq Fathanah's values ​​and professionalism in serving BSM Bondowoso customers. Penelitian ini bertujuan untuk mengetahui sejauh mana pelaksaanaan audit syariah pada lembaga keuangan syariahdalam meninjau kinerja karyawan. Selain itu fungsi audit syariah yaitu sebagai pengendalian sistem pengawasan, pemeriksaan pada lembaga keuangan syariah agar tetap pada kepatuhan prinsip-prinsip syariah dalam penerapan audit. Metode penelitian ini menggunakan metode kualitattif deskriptif diama pengkajian pada keadaan objek penelitian. Pada akhirnya akan di tarik sebuah kesimpulan dan di deskripsikan dengan teori yang sudah berlaku dan berkenaan dengan objek penelitian. Hasil penelitian ini adalah Penerapan konsep good coorporate govarnance dalam proses auidit syariah di BSM Bondowoso dimana konsep yang dimaksud adalah penerapan prisip-prisip syariah sebagai kepatuhan dalam proses audit kinerja karyawan yang diterapkan BSM Bondowoso, sedangkan proses audit syariah itu sendiri di tinjau dari beberapa anilai diantranya keadialan, kemitraan, keterbukaan, penerapan nilai-nilai dilakukan oleh pengawas internal saat melakukan proses audit oleh pengawas internal kepada semua karyawan tanpa terkeculai. Dalam konsep good coorporate governance tidak hanya di terpkan pada pelaksaan proses audit syariah saja bahkan BSM Bondowoso memberi reward dan punishmen kepada karywan yang menerapkan prinsip dan kepatuhan auidit syariah dan menjaga nama baik dan memajukan BSM Bondowoso serta melayani nasabah secara optimal dan melayani secara profesional dengan menerapkan nilai-niai siddiq, fathanah, profesional sbagai semboyan dan budaya kerja BSM Bondowoso. Dapat ditarik kesimpulan bahwa dalam penerapan audit syariah terhadap kinerja karyawan BSM diterapkan kepada semua karyawan tanpa terkrcuali dengan prinsip-prisip syariah, sedangkan dari konsep good coorporate govarnace ditinjau dari kinerja karyawan yang menerapkaan prinsip keadilan, kemitraan, serta keterbukan yang dilakukan oleh pengawas interna. Selain itu BSM Bondowoso memberikan reward dan punishmen kepada karyawan yang telah mmbantu mengembakan kemajuaan BSM Bondowoso dan bekerja secara profesional dan menerapkan nilai-nilai siddiq fathanah dan profesionalisme dalam melayani nasabah BSM Bondowoso